The world after COVID : a perspective from history (2020)
A mong the brilliant and flamboyant costumes they wear during Carnival in Venice, a sombre figure also stalks. It wears a white mask with dark spectacles and a long curving beak along with a black hat and gown. The “plague doctor” costume was once more than a diversion. It dates back to the middle of the 14th century when waves of the bubonic plague—the Black Death—hit the city, probably borne from further east by some of the many trading ships that had made Venice so rich. The authorities did what they could, setting up special burial grounds and quarantine stations throughout the city and eventually obliging newly arriving ships to isolate themselves for forty days on a remote island. The city also organized and paid for the plague doctors. The mask, with its spectacles and a beak stuffed with special herbs, would, it was hoped, ward off the noxious vapors suspected of carrying the disease. The great trading city of Genoa on the other side of Italy endured its own outbreak around the same time and the plague spread outwards throughout Europe, carrying off a third or more of all its inhabitants.